402 Effect of Antenatal Corticosteroids in Activity and Expression of Secretory Phospholipase A2 and TNF Alfa in Lung of Newborn Rats. (October 2012) - Remesal, A; Feliciano, L San; Luca, D de; Benito, D; Minucci, A; Isidoro-García, M; Ludeña, D
Abstract : Introduction: The sPLA2 plays an important role in the development of acute respiratory distress syndrome. It is regulated by many factors including steroids and TNFa. Antenatal corticosteroids are recommended for preventing respiratory distress syndrome in preterm infants. Recent studies suggest that betamethasone might be a better choice than dexamethasone. The aim of this study is evaluate differences between both antenatal corticosteroids in the regulation of sPLA2 and TNFa. Methods: Dexamethasone, betamethasone or saline were administered intravenously to pregnant Wistar rats on the 20 th and 21 st days of gestation. We evaluated pulmonary sPLA2 and TNFa mRNA in newborn rats at birth by RT-PCR. We also evaluated sPLA2 activity by an ultrasensitive non-radioactive method on microplate and the TNFa protein expression by ELISA. Differences between the groups were determined by one way ANOVA (p<0.05). Results: We observed a statistically significant decrease in the sPLA2 mRNA in the betamethasone (0.61) and dexamethasone (0.26) groups respect the control (1.05) group and a decrease in the sPLA2 activity in the betamethasone group (33.78) respect the control group (50.74). We observed a statistically significant decrease in the TNFa protein in the betamethasone group (472.61) respect the dexamethasone group (768.65). Conclusions: Antenatal glucocorticoids inhibits the expression of sPLA2 through the reduction of TNFa in the lung of newborn rats. These potential beneficial effects are more evident in the group treated with antenatal betamethasone. Our studies also support the notion that betamethasone could be the drug of choice for treating pregnant women at risk of preterm delivery.